Współpraca międzynarodowa i transgraniczna gminy we wspieraniu gospodarki lokalnej - Filipiak, Beata (International and Cross Border Cooperation of Self-Governments in Support of the Local Economy, 2006)
The article presents problems of international and cross border cooperation of self-government. r discusses the influence of international and cross border cooperation on the competitive-lf-governments. He analyzes the mode) of the cooperation between Polish and foreign self-governments and indicators of its choice. In the end desirable effects of cooperation are presented
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 264-273